2013
DOI: 10.1186/1471-2369-14-173
|View full text |Cite
|
Sign up to set email alerts
|

Impaired renal function impacts negatively on vascular stiffness in patients with coronary artery disease

Abstract: BackgroundChronic kidney disease (CKD) and coronary artery disease (CAD) are independently associated with increased vascular stiffness. We examined whether renal function contributes to vascular stiffness independently of CAD status.MethodsWe studied 160 patients with CAD and 169 subjects without CAD. The 4-variable MDRD formula was used to estimate glomerular filtration rate (eGFR); impaired renal function was defined as eGFR <60 mL/min. Carotid-femoral pulse wave velocity (PWV) was measured with the Sphygmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…Reduced GFR has been associated with central arterial stiffness in terms of a higher augmentation index (Andrade et al 2008). Coronary artery disease (CAD) patients with impaired renal function have greater cfPWV values compared to those with CAD and normal renal function (Rossi et al 2013). Our study showed that log-Cre is positively correlated with cfPWV values among our KT patients.…”
Section: Discussionsupporting
confidence: 58%
“…Reduced GFR has been associated with central arterial stiffness in terms of a higher augmentation index (Andrade et al 2008). Coronary artery disease (CAD) patients with impaired renal function have greater cfPWV values compared to those with CAD and normal renal function (Rossi et al 2013). Our study showed that log-Cre is positively correlated with cfPWV values among our KT patients.…”
Section: Discussionsupporting
confidence: 58%
“…30,31 Finally, AKI alters tissue healing and may potentially interfere with myocardial recovery after infarction. [32][33][34] Currently, patients with AKI are managed with supportive therapy because of the absence of specific strategies for established AKI. Almost all therapeutic agents that have been previously tested for this indication have failed to reach clinical practice, although some promising approaches in the prevention of AKI are being explored.…”
Section: Discussionmentioning
confidence: 99%
“…Of those, 424 use at least 1 of the arterial stiffness parameters outlined in this article, with the majority using cfPWV (314 articles) or AIx (159 articles). Many of these address large artery stiffness in disease, including but not limited to hypertension [32], renal disease [33], diabetes [34], coronary artery conditions [35,36], and heart failure [37], as well as postsurgical risk quantification such as in coronary artery intervention [38]. As review articles exist on arterial stiffness in these diseases elsewhere, and a thorough review of all would not be possible here, the remainder of this article addresses the population data gathered on SphygmoCor technology measurement of large artery stiffness, and the clinical use of these values.…”
Section: Clinical Evidence and Trialsmentioning
confidence: 99%